2020
DOI: 10.1038/s41433-020-01273-4
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of conjunctival naevi in children and adolescents

Abstract: Objective The objective of this study is to characterise the natural history of conjunctival naevi in a paediatric and adolescent population. Methods All children and adolescents referred to Moorfields Ocular Oncology Service for evaluation between January 2015 and 2020 were included. Exclusion criteria included age >20 years old and lack of anterior segment photographs. A total of 77 patients were included with a mean age of 12 years (standard deviation: 3.9; range, 4–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Some authors reported that conjunctival melanocyte lesions mainly affect girls [ 14 ], as we also recorded in the present study, but other authors stated that boys are more affected by this pathology [ 13 ]. Negretti et al (2021) pointed out that 95% of all the conjunctival nevi that they have analyzed were located on the bulbar conjunctiva, most common (53%) in the temporal horizontal quadrant, and often involving the limbus (57%) [ 13 ]. Some other authors reported that nevi are located in the interpalpebral bulbar conjunctiva (67–72%), the lacrimal caruncle (15–22%), and tarsus (0.7%) [ 15 , 16 ].…”
Section: ⧉ Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Some authors reported that conjunctival melanocyte lesions mainly affect girls [ 14 ], as we also recorded in the present study, but other authors stated that boys are more affected by this pathology [ 13 ]. Negretti et al (2021) pointed out that 95% of all the conjunctival nevi that they have analyzed were located on the bulbar conjunctiva, most common (53%) in the temporal horizontal quadrant, and often involving the limbus (57%) [ 13 ]. Some other authors reported that nevi are located in the interpalpebral bulbar conjunctiva (67–72%), the lacrimal caruncle (15–22%), and tarsus (0.7%) [ 15 , 16 ].…”
Section: ⧉ Discussionsupporting
confidence: 78%
“…Recently, in 2021, a group of researchers at Moorfields Eye Hospital, London (UK), evaluated over a six-years period all children and adolescents under the age of 20 who were diagnosed with a conjunctival nevus. Their series included a total of 77 patients with a mean age of 12 years (range: four to 20 years) [ 13 ].…”
Section: ⧉ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conjunctival pigmentation can occur following traumatic scleral tear repair or following microincisional vitreous surgery [1][2][3]. Such pigmentations can also be congenital or acquired following melanoma, drug induced, or other systemic illnesses [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%